Pengukuran Tingkat Kematangan Pengembangan Business Intelligence Teknologi Informasi dan Komunikasi (TIK) pada Perguruan Tinggi - Setiya Nugroho; Ardhin Primadewi; Uky Yudatama (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
In the era of globalization, the role of Information and Communication Technology (ICT) is the main asset in winning the global competition. Currently the role of ICT in education is enormous. High education have used ICT as an implementation of e-business. But the implementation of ICT business intelligence in high education still sporadic. High education need direction of measurable and targeted ICT development with business intelligence overview. It needs a reference of management and monitoring of ICT business intelligence implementation at high education as a benchmark. The benchmark in this study is using BIDM framework that can evaluate the development of business intelligence implementation from technological, human and process perspective. The result is a level in terms of implementation of ICT business intelligence in high education that became the basis of making the next strategic plan of higher education. Then the existing problems can be mapped using Value chain analysis. Combining these two ways is expected to be a reference for the development of implementation of ICT business intelligence in high education to be more systematic.